Stem Cell Transplantation as a Dynamical System: Are Clinical Outcomes Deterministic? - Toor, Amir A.; Kobulnicky, Jared D.; Salman, Salman; Roberts, Catherine H.; Jameson-Lee, Max; Meier, Jeremy; Scalora, Allison; Sheth, Nihar; Koparde, Vishal; Serrano, Myrna; Buck, Gregory A.; Clark, William B.; et al. (Frontiers in Immunology, 2014)
Outcomes in stem cell transplantation (SCT) are modeled using probability theory. However the clinical course following SCT appears to demonstrate many characteristics of dynamical systems, especially when outcomes are considered in the context of immune reconstitution. Dynamical systems tend to evolve over time according to mathematically determined rules. Characteristically, the future states of the system are predicated on the states preceding them, and there is sensitivity to initial conditions. In SCT, the interaction between donor T cells and the recipient may be considered as such a system in which, graft source, conditioning and early immunosuppression profoundly influence immune reconstitution over time. This eventually determines clinical outcomes, either the emergence of tolerance or the development of graft versus host disease. In this paper parallels between SCT and dynamical systems are explored and a conceptual framework for developing mathematical models to understand disparate transplant outcomes is proposed.